Pemberian Pembelajaran Ekstrakurikuler Mata Pelajaran PAI Di SDN 79 Lajae - Damayanti, Firda; Danial, Danial; Akhmad, Mawadda Warahmah; P, Sudirman; Ismail, Ismail (PANRITA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Extracurricular learning is the process of providing assistance to students in order to overcome the problems they face and to deepen their understanding of learning materials, especially religious basics, this is the basis for community service at SDN 79 Lajae because based on the results of observations made, the authors found that grade VI students still did not understand on basic religious material, especially in terms of the procedures for performing ablution and prayer, strengthening the material for the pillars of faith and the pillars of Islam, and providing material on moral aqidah. The importance of Islamic religious education for adolescents, one of which is applied in formal education, in this case elementary school, at this level of education, students are in a fertile situation to construct their religious understanding. The method used is the lecture method. The implementation of additional extracurricular activities is able to make further enhance their religious understanding. The implementation of providing additional learning shows that students experience an increase in knowledge in other words the lecture